The Gǝʿǝz Version of Philo of Carpasia’s Commentary on Canticle of Canticles 1:2–14a: Introductory Notes - Abraha, Tedros (Aethiopica, 2012)
The aim of the paper is to provide an overview of little known Gǝʿǝz texts ascribed to Philo, namely: fragments of a Paschal Homily, a bulky but incomplete commentary on the Pauline Corpus and a fragment of Philo of Carpasia’s commentary on the Canticle of Canticles. While concentrating mainly on the latter, the present article wants to draw attention to linguistic characteristics common to the trilogy which is associated with the name Philo. The Gǝʿǝz version of Philo of Carpasia’s Commentary is a rare example of a strictly paratactic translation which is keen to reproduce literally the Greek text from which it depended. The outcome is a hardly understandable Gǝʿǝz text which is however interesting as a unique witness of an ancient translation technique. The Philonian trilogy is among other aspects, a mine of unknown or little attested Gǝʿǝz terms.